Capital Structure and Adjustment Speed: Evidence From Listed Manufacturing Firms in Indonesia and Malaysia - Memon, Pervaiz Ahmed; Shah Syed, Mir Muhammad; Ghumro, Niaz Hussain; Rus, Rohani Md (The Indonesian Capital Market Review, 2019)
This paper identifies factors determining capital structure and estimates the speed at which firmsadjust to optimal debt in Malaysian and Indonesian manufacturing firms. It uses the difference Generalized Method of Moments (GMM) estimator and the partial adjustment model in a sample of 141 Malaysian and 96 Indonesian firms, which include many of the major manufacture companies in these economies. The results suggest the existence of dynamic capital structure in both countries, but differences in adjustment speed towards optimal debt and factors affecting the optimal debt levels are evident between these countries. Firm-specific factors such as tangibility of assets, non-debt tax shield, and profitability significantly affect optimal debt in both countries. However, most countryspecific factors are insignificant determinants, GDP in Malaysia being the sole exception. The findings of this study are helpful for corporate managers, policymakers, and regulatory authorities in monitoring the amount of debt used by the firms and their adjustment speed towards target debt to avoid the bankruptcies. Financial reforms can be worked out in these economies to better support the firms in use of optimal debt.